Research progress on molecular biomarkers of acute myeloid leukemia - Yin, Pei-Yuan; Wang, Rui-Wen; Jing, Rui; Li, Xing; Ma, Jing-Hua; Li, Kai-Min; Wang, Hua (Frontiers in Oncology, 2023)
Acute myeloid leukemia (AML) is the most common type of adult acute leukemia. The pathophysiology of the disease has been studied intensively at the cellular and molecular levels. At present, cytogenetic markers are an important basis for the early diagnosis, prognostic stratification and treatment of AML. However, with the emergence of new technologies, the detection of other molecular markers, such as gene mutations and epigenetic changes, began to play important roles in evaluating the occurrence and development of diseases. Recent evidence shows that identifying new AML biomarkers contributes to a better understanding of the molecular mechanism of the disease and is essential for AML screening, diagnosis, prognosis monitoring, and individualized treatment response. This article reviewed the molecular biomarkers related to AML and discussed their clinical significance from the aspects of risk prediction, diagnosis and prognosis to provide a reference for the precise diagnosis and treatment of AML.